2017
DOI: 10.1111/chso.12223
|View full text |Cite
|
Sign up to set email alerts
|

Defining Social Inclusion for Children with Disabilities: A Critical Literature Review

Abstract: Social inclusion is a complex and often misunderstood concept. For children with disabilities, research has documented the degree of loneliness, bullying and exclusion they often experience in their social lives. This paper presents the findings of a critical literature review on the social inclusion of children with disabilities. Study methods comprised rigorous criteria for study selection followed by established protocols for evaluating studies. Reputable rating scales were used to examine peer-reviewed res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 75 publications
1
42
0
Order By: Relevance
“…This review aimed to provide an overview of the scientific literature in order to identify the main factors influencing participation in sport intervention programs (SIPs) in people with ID. Recently, there has been an increased interest in sport programs addressed to individuals with ID given the sport educational values and their efficacy in improving physical and mental health [ 20 , 36 , 37 , 42 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review aimed to provide an overview of the scientific literature in order to identify the main factors influencing participation in sport intervention programs (SIPs) in people with ID. Recently, there has been an increased interest in sport programs addressed to individuals with ID given the sport educational values and their efficacy in improving physical and mental health [ 20 , 36 , 37 , 42 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a wide variety of methodological variables such as participants’ age and disability, intervention characteristics, context, and measures, the main factors essential for the people with ID experiencing SIPs were revealed to concern suitable places for the SIP development, adequate implementation of PA programs in the school and extra-school contexts, and the education and training of teachers and instructors. Studies underlined the importance of providing access to physical exercise for people with ID through recreational and competitive sport and physical education curricula [ 20 , 22 , 36 , 37 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of young children with disabilities attend an early childhood program with their typically developing peers (U.S. Department of Education, 2013). High-quality inclusive practices promote the physical and social integration of children with disabilities in classrooms and communities, so they can build a sense of community as a member of the society and form positive relationships with their typically developing peers (Guralnick, 2001;Koller, Le Pouesard, & Rummens, 2018;Odom, Buysse, & Soukakou, 2011). However, children with disabilities are not frequently socially included by their typically developing peers in classroom interactions especially during the time when peer interactions were more likely to occur than adult-child interactions, such as free play time (Brown, Odom, Li, & Zercher, 1999;Guralnick, 1999;Odom, Favazza, Brown, & Horn, 2000;Odom et al, 2004).…”
mentioning
confidence: 99%
“…A research done by Cummins and Lau (2003) showed that exceptional children or children with disability were stayed on the risk of being isolated and intimidated than the other normal children. Similar to Cummins and Lau, although exceptional children were still having ability to interact with friends and participate in community activity, but they were still having the low social integration level (Koller, Pouesard and Rummens, 2018).…”
Section: Social Inclusionmentioning
confidence: 84%